Normal Developable Surfaces of A Surface Along A Direction Curve - Abdel-Sattar, Rashad Abdel-Baky; Unluturk, Yasin (Journal of the Indonesian Mathematical Society, 2020)
We construct a developable surface normal to a surface along a curve on the surface. As differs from the work Hananoi, we choose the curve as the normal direction curve on which the new surface is formed in Euclidean space. We obtain some results about the uniqueness and the singularities of such developable surfaces. We also give two invariants of curves on a surface which characterize singularities.